TED TALKS BASED LEARNING ON STUDENTS’ INTERMEDIATE SPEAKING SKILLS LEVEL - Ainul Yaqin; Tera Athena (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
The top investments for all people around the world are improving and mastering speaking skills. The researcher tried to look at the implementation of TED Talks Video based learning on students’ speaking skill. In addition, this research is expected to be given as a reference, source of knowledge, theory for future and motivate readers to use TED Talks video implementation in teaching and learning. In this research, the researcher used a qualitative method with a case study approach. The researcher wanted to explain about how are the implementation of TED Talks video based learning on students’ speaking skill and the students’ responses through the teaching and learning. The result showed that the students are interested because they can learn English with full of fun in speaking skill as well to increase their speaking skill itself, pronunciation, accent and all knowledge about speaking. Besides, they also feel motivated to join the teaching and learning using TED Talks video because there are lots of advantages, such as can learn about the body gesture while speaking and get lots of motivation and information from the TED Talks video. Finally, the students feel enjoy to retell or practice in speaking class.